Vegan mac & cheese : more than 50 plant-based recipes for the ultimate comfort food - Robertson, Robin (Robin G.) (Harvard Common Press, 2019)
"Who says vegans can't have macaroni and cheese? In this inspiring volume by best-selling vegan author Robin Robertson, you will find more than 50 awesome plant-based recipes for deeply flavorful dishes that take this timeless comfort food in exciting new directions. Like most people, chances are you've eaten a lot of macaroni and cheese in your life. If you're new to a plant-based diet, you might be wondering if you can still enjoy this comforting meal. You'll be happy to know the answer is "Yes!" Robin shows you how to make what she calls Mac Uncheese-rich, delectable pasta dishes featuring vegan cheese sauces that start with plant milks, vegetables, and nuts as their base ingredients. Using these sauces-or, if you prefer, using store-bought vegan cheese-you can make many tempting variants of the cheesy pasta dish, from the familiar and homey, such as Mom's Classic Mac UnCheese, to the globally adventuresome, such as Indian Curry Mac or Salsa Mac and Queso. An entire chapter is devoted to veggie-loaded mac and cheese dishes, like Buffalo Cauliflower Mac, Arugula Pesto Mac UnCheese, or Smoky Mac and Peas with Mushroom Bacon. Another chapter serves up meatless mac and cheeses made meaty with lentils, jackfruit, mushrooms, and more. And, for delicious fun, there are recipes for Mac and Cheese Balls, Mac 'n' Cheese Pizza, Waffled Mac and Cheese, and Cheesy Mac Muffins. In addition to the recipes, Vegan Mac and Cheese features lists of toppings, add-ins, and other ways to be creative with these plant-based mac and cheese recipes, which will warm your soul all year long"--